Electrolyte, preparation method thereof and battery
By designing an electrolyte containing fluorine lithium salt, solvent and diluent, the problem of poor circulation stability and safety of lithium metal batteries is solved, efficient lithium ion transmission and stable interface layer formation are achieved, and the performance of lithium metal batteries is significantly improved.
Patent Information
- Application Number
- CN202510087392.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
AI Technical Summary
In the prior art, the lithium metal battery has low cyclic stability and poor safety, mainly due to the poor ion conductivity of the electrolyte and the uneven peeling/deposition of metal lithium.
By designing an electrolyte, which is mainly made of fluorine-containing lithium salts, solvents and diluents, with a molar ratio range of (0.8~1.8): (1~3): (1~5), to build a high-concentration electrolyte system, form a solvation structure dominated by anions, and promote the formation of a stable interface layer (SEI interface) rich in inorganic substances during the cycle charging and discharge process of lithium metal batteries, thereby adjusting the lithium peeling/deposition morphology and inhibiting dendrites' growth and side reactions.
The cycle stability and safety of lithium metal batteries have been significantly improved, while taking into account the ion conductivity of the electrolyte, which has promoted the widespread application of lithium metal batteries.
Smart Images

Figure CN119920979A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to an electrolyte, a preparation method thereof, and a battery. Background Art
[0002] Lithium metal has an ultra-high theoretical specific capacity (3860mAh / g) and a low reduction potential (-3.04V), making it one of the ideal materials for lithium battery electrodes. Compared with traditional intercalated graphite anodes, lithium metal anodes have long dendrites and accumulation during the charge and discharge cycle, as well as continuous side reactions with the electrolyte, which causes uneven stripping / deposition of lithium metal, forming a large amount of dead lithium, which in turn leads to low cycle stability and poor safety of lithium metal batteries.
[0003] Among the various factors that affect the performance of lithium metal batteries, the electrolyte plays a leading role. Therefore, in the prior art, the salt concentration in the electrolyte is increased in the hope of improving the cycle stability and safety of lithium metal batteries. However, high-salt concentration electrolytes have the defect of poor wettability, which greatly reduces the contact area between the pole pieces, diaphragms and electrolytes inside the battery cell, seriously hinders the transmission of lithium ions in the electrolyte, thereby reducing the number of battery cycles, and ultimately restricting the widespread application of lithium metal batteries.
[0004] In view of this, this application is hereby filed. Summary of the invention
[0005] In view of the above, the present application provides an electrolyte, a preparation method thereof and a battery, aiming to solve the problems in the prior art of poor ion conductivity of the electrolyte, low cycle stability and poor safety of lithium metal batteries.
[0006] The first aspect of the present application provides an electrolyte, which is mainly made of a fluorine-containing lithium salt, a solvent and a diluent; the molar ratio of the fluorine-containing lithium salt, the solvent and the diluent is (0.8-1.8): (1-3): (1-5).
[0007] The electrolyte provided by the present invention is mainly prepared from a fluorine-containing lithium salt, a solvent and a diluent in a molar ratio within the range of (0.8-1.8):(1-3):(1-5). By designing the components of the electrolyte, the electrolyte obtained is a high-concentration electrolyte system, and the electrolyte can form a solvation structure mainly composed of anions, so that a lithium metal battery forms a stable interface layer (SEI interface) rich in inorganic substances to passivate metallic lithium during the cyclic charge and discharge process, thereby achieving the regulation of lithium stripping / deposition morphology, inhibiting the growth of lithium dendrites and reducing the continuous side reactions between lithium metal and the electrolyte.
[0008] Specifically, when the lithium metal battery is cycled, the electrolyte can generate a variety of SEI structures of quasi-mosaic (quasi-inlay) and multi-layer types. In the quasi-mosaic SEI structure, inorganic nanoparticles are randomly distributed in the organic matrix, while in the multi-layer SEI structure, the inorganic layer and the organic layer are evenly arranged to form a layered ordered structure. The fluorine-containing lithium salt in the above molar ratio range is dissolved in the solvent, and the decomposition of the fluorine-containing lithium salt is dominant when the lithium metal battery is cycled, which is conducive to promoting the electrolyte to generate a multi-layer SEI structure during the cycle, so as to increase the interfacial energy of the SEI interface, thereby inhibiting the growth of lithium dendrites and ensuring the cycle stability and safety of the lithium metal battery.
[0009] In addition, the solvent design within the above molar ratio range helps to improve the compatibility of the solvent with metallic lithium, and promotes the formation of a more stable SEI layer during the cycle of the lithium metal battery; on the other hand, the solubility of the fluorinated lithium salt in the diluent is low, that is, the diluent does not completely participate in the solvation of the fluorinated lithium salt, but can greatly alleviate the poor wettability and high viscosity of the electrolyte caused by the high concentration of lithium salt, thereby improving the ion conductivity of the electrolyte; it should be emphasized that the complex formed by the fluorinated lithium salt and the solvent has a large miscibility with the diluent, mainly due to the strong mutual solubility of the diluent and the solvent molecules, forcing fewer solvent molecules to enter the first solvation sheath layer, and more diluent is distributed in the second solvation sheath layer. This distribution method can allow more anions decomposed from the fluorinated lithium salt to enter the cation solvation inner sheath layer, so as to be reduced on the metallic lithium negative electrode to form a more stable interface layer, thereby increasing the lithium content on the metallic lithium negative electrode during the cycle, making the lithium deposition on the metallic lithium negative electrode more dense and uniform, and ultimately significantly improving the cycle stability and safety of the lithium metal battery.
[0010] In some embodiments, the electrolyte further includes an additive; the additive includes at least one of an organic compound and an inorganic compound; the molar ratio of the fluorine-containing lithium salt, the solvent, the diluent and the additive is (0.8-1.8): (1-3): (1-5): (0.01-2).
[0011] Based on the molar ratio of fluorinated lithium salt, solvent and diluent in the electrolyte being (0.8-1.8):(1-3):(1-5), additives within the above molar ratio range are further compounded in the fluorinated lithium salt, solvent and diluent. Since the fluorinated lithium salt has good solvation ability, the organic compound in the additive can effectively inhibit its solvation ability and promote the anion reduction and decomposition of the electrolyte during the cyclic charge and discharge process to generate a large amount of inorganic products, thereby making the SEI interface layer rich in inorganic components, thereby improving the lithium ion transmission capacity at the SEI interface; at the same time, the organic compound also helps to generate highly polymerized long-chain organic polymers to improve the elasticity of the SEI interface layer, so that the SEI interface layer can fully adapt to the volume change of lithium metal, avoid the collapse of the SEI interface layer structure, and achieve the improvement of the cycle stability of the lithium metal battery; and the inorganic compound can further increase the inorganic components rich in the SEI interface layer, further improving the electrode reaction kinetics.
[0012] Therefore, the electrolyte prepared by the coordinated combination of fluorine-containing lithium salts, solvents, diluents and additives within the above-mentioned molar ratio range can effectively inhibit the growth and accumulation of lithium metal dendrites during the cyclic charge and discharge process of lithium metal batteries, reduce the continuous side reactions between lithium metal electrodes and electrolytes, improve the cyclic stability and safety of lithium metal batteries, and at the same time take into account the ion conductivity of the electrolyte to promote the widespread application of lithium metal batteries.
[0013] In some embodiments, the solvent includes at least one of an ester compound A and an ether compound A; and the diluent includes at least one of a halogenated alkane compound, an ester compound B and an ether compound B.
[0014] In some embodiments, the organic compound has a monoether oxygen functional group and / or an unsaturated cyclic structure; optionally, the inorganic compound includes at least one of a nitrogen-containing lithium salt and a lithium halide salt.
[0015] In some embodiments, the additive satisfies at least one of the following a to c:
[0016] a. The organic compound has any one or more of a three-membered ring, a four-membered ring, a five-membered ring or a six-membered ring, and the ring structure contains at least one ether bond; optionally, the ring structure has at least one substituent selected from alkyl, halogenated alkyl, nitro, hydroxyl and oxalylamino groups;
[0017] b. The organic compound includes at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran and trioxymethylene;
[0018] c. The inorganic compound includes at least one of lithium nitrate, lithium fluoride, lithium bromide, lithium iodide and lithium chloride.
[0019] In some embodiments, the additive is a mixture of lithium nitrate and at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran, and trioxymethylene.
[0020] In some embodiments, the diluent satisfies at least one of the following conditions:
[0021] d. The halogenated alkane compound includes at least one of decafluoropentane, methoxy nonafluorobutane, and ethoxy nonafluorobutane;
[0022] e. the ester compound B includes a fluorinated carbonate, which may be selected from at least one of fluoroethylene carbonate, 1,2-bis(2-fluoroethoxy)ethane, methyl trifluoroethyl carbonate, ethyl difluoroacetate, ethyl trifluoroacetate, tris(2,2,2-trifluoroethyl)orthoformate, methyl pentafluoropropionate, and ethyl pentafluoropropionate;
[0023] f. The ether compound B includes a fluoroether, which can be selected from at least one of 2,2-bis(trifluoromethyl)-1,3-dioxolane, tetrafluoro-1-(2,2,2-trifluoroethoxy)ethane, methoxyperfluorobutane, 1,1,1,3,3,3-hexafluoroisopropyl methyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, and 1,1,2,2,-tetrafluoroethyl-2,2,2-trifluoroethyl ether.
[0024] In some embodiments, the solvent satisfies at least one of the following g to h:
[0025] g. the ester compound A comprises at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, vinylene carbonate, methylene ethylene carbonate, methyl butyrate, ethyl propionate, trimethyl phosphate, triethyl phosphate, γ-butyrolactone, triallylamine, triallyl cyanurate, and triallyl isocyanurate;
[0026] h. The ether compound A includes aliphatic ether, which can be selected from at least one of methyl n-butyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, ethylene glycol dibutyl ether, 1,2-dimethoxypropane, 1,3-dimethoxypropane, and allyl ether.
[0027] In some embodiments, the concentration of the fluorine-containing lithium salt in the solvent is 4 to 8 mol / L.
[0028] In some embodiments, the fluorine-containing lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; optionally, the fluorine-containing lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.
[0029] The second aspect of the present invention provides a method for preparing the above-mentioned electrolyte, wherein a fluorine-containing lithium salt, a solvent, and a diluent are mixed in a predetermined ratio to obtain an electrolyte; optionally, a fluorine-containing lithium salt, a solvent, a diluent and an additive are mixed in a predetermined ratio to obtain an electrolyte.
[0030] A third aspect of the present invention provides a battery, which is at least formed by the electrolyte assembly as described above.
[0031] The electrolyte, preparation method thereof and other features and advantages of the battery provided by the present invention are described in detail in the subsequent specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 This is a cycle test diagram of a lithium metal soft-pack battery prepared with the electrolyte of Example 1 of the present invention;
[0034] Figure 2 This is a cycle test diagram of a lithium metal soft-pack battery prepared with the electrolyte of Example 3 of the present invention;
[0035] Figure 3 This is a cycle test diagram of a lithium metal soft-pack battery prepared with the electrolyte of Example 5 of the present invention;
[0036] Figure 4 This is a cycle test diagram of a lithium metal soft-pack battery prepared with the electrolyte of Comparative Example 1 of the present invention;
[0037] Figure 5 This is a cycle test diagram of a lithium metal soft-pack battery prepared with the electrolyte of Comparative Example 2 of the present invention;
[0038] Figure 6 The cycle test diagram and CV curve diagram of the lithium metal soft-pack battery prepared by the electrolyte of Example 9 of the present invention;
[0039] Figure 7This is a cycle test diagram of a lithium metal soft-pack battery prepared with the electrolyte of Example 17 of the present invention;
[0040] Figure 8 The LSV curve of the lithium-copper half-cell prepared by the electrolyte of Comparative Example 7 of the present invention;
[0041] Fig. 9 The LSV curve of the lithium-copper half-cell prepared by the electrolyte of Comparative Example 9 of the present invention;
[0042] Fig.10 This is the LSV curve of the lithium-copper half-cell prepared with the electrolyte of Comparative Example 10 of the present invention. DETAILED DESCRIPTION
[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0044] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0045] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0046] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may also include or contain other components not listed, or may only include or contain the listed components.
[0048] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0049] Based on the foregoing, the general inventive concept of the embodiments of the present application is to provide an electrolyte, wherein the components of the electrolyte are designed, and the electrolyte is mainly made of a fluorine-containing lithium salt, a solvent and a diluent, wherein the molar ratio of the fluorine-containing lithium salt, the solvent and the diluent is (0.8-1.8):(1-3):(1-5); thereby, a high-concentration electrolyte system is constructed, and through the synergistic effect of the components within the above-mentioned molar ratio range, the ion conductivity of the electrolyte is improved, while the cycle stability and safety of the lithium metal battery are improved.
[0050] In this embodiment, the molar ratio of the fluorine-containing lithium salt, the solvent and the diluent is (0.8-1.8):(1-3):(1-5); illustratively, the molar ratio of the fluorine-containing lithium salt, the solvent and the diluent can be 0.8:1:1, 0.9:1:1, 1:1:1, 1.1:1:1, 1.2:1:1, 1.3:1:1, 1.4:1:1, 1.5:1:1, 1.6:1:1, 1.7:1:1, 1.8:1:1, 0 ... :1.6:1, 0.8:1.8:1, 0.8:2:1, 0.8:2.2:1, 0.8:2.4:1, 0.8:2.6:1, 0.8:2.8:1, 0.8:3:1, 0.8:1:1.5, 0.8:1:2, 0.8:1:2.5, 0.8:1:3, 0.8:1:3.5, 0.8:1:4, 0.8:1:4.5, 0.8:1:5 or any molar ratio within the range of (0.8-1.8):(1-3):(1-5).
[0051] It should be understood that the high-concentration electrolyte in the present application refers to an electrolyte in which the lithium salt concentration, ie, the ratio of the amount of lithium salt substance to the volume of the solvent, is above 3M.
[0052] It should be noted that the diluent provided in the embodiments of the present application can not only reduce the viscosity of the electrolyte and improve the conductivity of the electrolyte in the electrolyte system, but also affect the components of the interface film by participating in the cation solvation sheath, so that more anions enter the cation solvation sheath, so as to improve the film formation stability of the SEI and CEI interface layers, thereby improving the ion conductivity of the electrolyte while enhancing the cycle stability of the lithium metal battery.
[0053] The "solvation sheath" in this application refers to an ordered structure of a layer of solvent molecules formed by solvent molecules around ions in the electrolyte. Solvent molecules bind to ions in the solvation sheath through hydrogen bonds, electrostatic effects, van der Waals forces and other interaction forces. The existence of the solvation sheath can affect the reaction rate, transmission properties and solubility of ions. The solvent sheath can be used to characterize the changing process of solvent particles binding to solute particles. The "first solvation sheath" in this application refers to a layer of solvation sheath that is closest to the solvent molecules of lithium ions. The radius of the first solvent sheath can be used to characterize the range of the nearest layer of lithium ions binding to the solvent. The "second solvation sheath" is compounded on the first solvent sheath and is farther away from the lithium ions than the first solvent sheath. In the embodiments of this application, the diluent can regulate the reaction rate and transmission properties of ions by participating in the composition of the cation solvation sheath.
[0054] In addition, the "SEI" in this application refers to the solid electrolyte interface layer (Solid Electrolyte Interphase), specifically a thin film formed between the positive electrode, negative electrode and electrolyte of a lithium battery. A good SEI interface layer allows lithium ions to pass freely and blocks the passage of other components, thereby inhibiting the positive and negative electrodes from reacting with the electrolyte again, so as to promote the lithium battery to achieve a longer service life, energy storage capacity, and environmental adaptability. Improved performance. In addition, the "CEI" in this application refers to the cathode-electrolyte interface (Cathode-Electrolyte Interface). The CEI interface layer is the interface layer formed between the cathode material and the electrolyte in the battery. In a lithium battery, the interaction between the cathode material and the electrolyte will affect the embedding and de-embedding process of lithium ions, thereby affecting the energy density and cycle life of the battery. Optimizing the formation and stability of the CEI interface is also an important factor in improving the performance of lithium batteries.
[0055] It should be made clear that the rapid depletion of active lithium and electrolyte during the cycle of lithium metal batteries is the key reason for the attenuation of the cycle life of lithium metal batteries. The SEI interface layer, as a nanoscale passivation layer between lithium and electrolyte, can inhibit the continuous reaction of lithium and electrolyte. At the same time, the SEI interface with poor stability will be repeatedly generated during the cycle of lithium metal batteries, resulting in continuous reaction and consumption of electrolyte and active lithium, aggravating the deterioration of the cycle stability of lithium metal batteries. Therefore, improving the stability and uniformity of the SEI interface layer is crucial to improving the cycle life and cycle stability of lithium metal batteries.
[0056] In order to further improve the structural stability of the SEI interface layer and improve the transmission capacity of lithium ions at the SEI interface, the electrolyte provided in this embodiment also includes an additive; the additive includes at least one of an organic compound and an inorganic compound; wherein the molar ratio of the fluorine-containing lithium salt, the solvent, the diluent and the additive is (0.8-1.8):(1-3):(1-5):(0.01-2).
[0057] In this embodiment, the molar ratio of the fluorine-containing lithium salt, the solvent, the diluent and the additive is (0.8-1.8):(1-3):(1-5):(0.01-2); illustratively, the molar ratio of the fluorine-containing lithium salt, the solvent, the diluent and the additive can be 0.8:1:1:0.01, 0.9:1:1:0.02, 1:1:1:0.03, 1.1:1:1:0.04, 1.2:1:1:0.05, 1.3:1:1:0.06, 1.4:1:1:0.07, 1.5:1:1:0.08, 1.6:1:1:0.09, 1.7:1:1:0.1, 1.8:1:1:0.11, 0.8:1.2:1:0.12, 0.8:1.4:1 : 0.13, 0.8: 1.6: 1: 0.14, 0.8: 1.8: 1: 0.15, 0.8: 2: 1: 0.16, 0.8: 2.2: 1: 0.17, 0.8: 2.4: 1: 0.18, 0.8: 2.6: 1: 0.19, 0.8: 2.8: 1: 0.2, 0.8: 3: 1: 0.03, 0.8 : 1: 1.5: 0.06, 0.8: 1: 2: 0.08, 0.8: 1: 2.5: 0.1, 0.8: 1: 3: 0.12, 0.8: 1: 3.5: 0.14, 0.8: 1: 4: 0.16, 0.8: 1: 4.5: 0.18, 0.8: 1: 5: 0.2, 0.8: 1: 1: 0.21, 0.9: 1 :1:0.22, 1:1:1:0.23, 1.1:1:1:0.24, 1.2:1:1:0.25, 1.3:1:1:0.26, 1.4:1:1:0.27, 1.5:1:1:0.28, 1.6:1:1:0.29, 1.7:1:1:0.3, 1.8:1:1:0.31, 0. 8:1.2:1:0.32、0.8:1.4:1:0.33、0.8:1.6:1:0.34、0.8:1.8:1:0.35、0.8:2:1:0.36、0.8:2.2:1:0.37、0.8:2.4:1:0.38、0.8:2.6:1:0.39、0.8:2.8: 1:0.4, 0.8:2.9:1:0.5, 0.8:3:1:0.6, 0.8:3:1:0.7, 0.8:1:1.5:0.8, 0.8:2:2:0.9, 0.8:2.2:2.5:1, 0.8:2.4:3:1.1, 0.8:2.6:3.5:1.2, 0.8:2.8:4: 1.3, 0.8: 1.2: 4.5: 1.4, 0.8: 1.4: 5: 1.5, 0.8: 1.6: 1: 1.6, 0.8: 1.8: 2: 1.7, 0.8: 2: 3: 1.8, 0.8: 2.2: 4: 1.9, 0.8: 2.4: 5: 2 or (0.8~1.8): (1~3): (1~5): (0.Any molar ratio within the range of 01 to 2).
[0058] It can be understood that the additives in the embodiments of the present application can be organic compounds, inorganic compounds, or even mixtures of organic compounds and inorganic compounds; organic compounds as additives can inhibit the solvation ability of fluorine-containing lithium salts, so that the fluorine-containing lithium salts can decompose and generate more inorganic products during the cyclic charge and discharge process of the electrolyte, prompting the anions in the electrolyte to preferentially form the SEI interface layer, thereby increasing the proportion of inorganic components in the components of the SEI interface layer region, thereby improving the lithium ion transmission capacity of the SEI interface, and improving the ion conductivity of the electrolyte; at the same time, organic compounds can also generate highly polymerized long-chain organic polymers, which help to enhance the elasticity of the SEI interface layer, thereby improving the structural stability of the SEI interface layer, and improving the cycle stability and cycle life of the lithium metal battery; in addition, inorganic compounds as additives can further increase the proportion of inorganic components in the components of the SEI interface layer region, so as to significantly enhance the electrode reaction kinetics. The electrolyte prepared by the coordinated combination of fluorine-containing lithium salts, solvents, diluents and additives within the above-mentioned molar ratio range can effectively inhibit the growth and accumulation of lithium metal dendrites during the cyclic charge and discharge process of lithium metal batteries, reduce the continuous side reactions between lithium metal electrodes and electrolytes, improve the cyclic stability and safety of lithium metal batteries, and at the same time take into account the ion conductivity of the electrolyte.
[0059] In some embodiments, the solvent includes at least one of an ester compound A and an ether compound A; the electrolyte is prepared by selecting at least one of an ester compound A and an ether compound A as a solvent, and the ester compound A has an electron donor part (lithium ion receptor site) adjacent to the conjugated structure, so that the ester compound A as a solvent exhibits excellent antioxidant properties in the electrolyte to inhibit the continuous reaction between the electrolyte and the electrode, thereby enhancing the cycle stability of the lithium metal battery; and the ether compound A has good compatibility with metallic lithium, which is conducive to promoting the formation of a more stable SEI interface layer, so as to synergistically improve the cycle stability and cycle life of the lithium metal battery.
[0060] In some embodiments, the diluent includes at least one of a halogenated alkane compound, an ester compound B, and an ether compound B. The halogenated alkane compound, the ester compound B, and the ether compound B in the diluent are not miscible with the fluorine-containing lithium salt, so as to facilitate the dilution of the high-concentration electrolyte, thereby reducing the viscosity of the electrolyte, improving its wettability, and promoting the improvement of the ionic conductivity of the electrolyte; it should be clear that the halogenated alkane compound, the ester compound B, and the ether compound B are used as diluents, so that the diluent has a non-polar structure and low donor capacity to inhibit the oxidizing property of the electrolyte; and the diluent has a large miscibility with the complex of the fluorine-containing lithium salt and the solvent, and it participates in the formation of the cation solvation sheath, so that more anions enter the cation solvation sheath, and promotes the SEI interface layer and the CEI interface layer to have better film-forming stability, so as to improve the conductivity of the electrolyte and the cycle stability and cycle life of the lithium metal battery.
[0061] In some embodiments, the organic compound in the additive has a monoether oxygen functional group and / or an unsaturated cyclic structure. By designing an organic compound with a monoether oxygen functional group and / or an unsaturated cyclic structure, the monoether oxygen functional group can weaken the solvation ability of the fluorine-containing lithium salt and promote the reduction and decomposition of anions to generate a large amount of inorganic products to improve the conductivity of the electrolyte; while the unsaturated cyclic structure is prone to ring-opening polymerization to produce highly polymerized long-chain organic polymers to improve the structural stability of the SEI interface layer, thereby improving the cycle stability and cycle life of the lithium metal battery. In addition, the inorganic compound includes at least one of a nitrogen-containing lithium salt and a lithium halide salt; using a nitrogen-containing lithium salt and a lithium halide salt as an additive can increase the proportion of inorganic components in the SEI interface layer region components during the cycle of the lithium metal battery, thereby enhancing the electrode reaction kinetics.
[0062] In some embodiments, the organic compound has any one or more of a three-membered ring, a four-membered ring, a five-membered ring or a six-membered ring, and the ring structure contains at least one ether bond. By designing the organic compound as a cyclic ether compound, the organic compound weakens the solvation ability of the fluorine-containing lithium salt, and a ring-opening polymerization reaction occurs during the circulation process, thereby producing a highly polymerized long-chain organic polymer, so that the structural stability of the SEI interface layer is improved; it can be understood that the organic compound can have any one of a three-membered ring, a four-membered ring, a five-membered ring or a six-membered ring alone, and can also have a three-membered ring, a four-membered ring, a five-membered ring or a six-membered ring at the same time. There are multiple cyclic structures in the ring. The cyclic structure of the organic compound may contain one ether bond or two or more ether bonds. For example, when the organic compound has a three-membered ring structure and has one ether bond, it may be ethylene oxide, when the organic compound has a five-membered ring structure and has one ether bond, it may be tetrahydrofuran, when the organic compound has a five-membered ring structure and has two ether bonds, it may be 1,3-dioxolane, when the organic compound has a six-membered ring structure and has one ether bond, it may be tetrahydropyran, and when the organic compound has a six-membered ring structure and has three ether bonds, it may be trioxymethylene.
[0063] In some embodiments, the cyclic structure of the organic compound has at least one substituent selected from the group consisting of alkyl, halogenated alkyl, nitro, hydroxyl, and oxalylamino. For example, the cyclic structure of the organic compound having the above substituents may be 2-methyltetrahydrofuran, 2-ethyltetrahydrofuran, or isosorbide nitrate and the like. As additives, they can weaken the solvation ability of the fluorinated lithium salt and are prone to undergoing ring-opening polymerization during the cycle of the lithium metal battery, thereby effectively improving the cycle stability and cycle life of the lithium metal battery.
[0064] In some embodiments, the organic compound includes at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran, and trioxymethylene; tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran, and trioxymethylene all have monoether oxygen functional groups and / or unsaturated cyclic structures, and as additives can promote the reduction and decomposition of anions to generate inorganic products, as well as produce highly polymerized long-chain organic polymers.
[0065] In some embodiments, the inorganic compound includes at least one of lithium nitrate, lithium fluoride, lithium bromide, lithium iodide, and lithium chloride. Lithium nitrate, lithium fluoride, lithium bromide, lithium iodide, and lithium chloride as additives can further increase the proportion of inorganic components in the SEI interface layer to enhance the electrode reaction kinetics.
[0066] In some embodiments, the additive is a mixture of lithium nitrate and at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran, trioxymethylene.
[0067] It can be understood that the electrolyte in the embodiments of the present application can use only one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran, and trioxymethylene as additives, or only lithium nitrate as an additive, or a mixture of lithium nitrate and any one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran, and trioxymethylene as an additive, all of which can effectively improve the ion conductivity of the electrolyte, as well as the cycle stability and cycle life of the lithium metal battery.
[0068] In some embodiments, in the diluent, the halogenated alkane compound may include at least one of decafluoropentane, methoxy nonafluorobutane, and ethoxy nonafluorobutane; the ester compound B includes a fluorinated carbonate, which may be selected from at least one of fluoroethylene carbonate, 1,2-bis(2-fluoroethoxy)ethane, methyl trifluoroethyl carbonate, ethyl difluoroacetate, ethyl trifluoroacetate, tris(2,2,2-trifluoroethyl)orthoformate, methyl pentafluoropropionate, and ethyl pentafluoropropionate; the ether compound The compound is a fluoroether, which may include at least one of 2,2-bis(trifluoromethyl)-1,3-dioxolane, tetrafluoro-1-(2,2,2-trifluoroethoxy)ethane, methoxyperfluorobutane, 1,1,1,3,3,3-hexafluoroisopropyl methyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, and 1,1,2,2,-tetrafluoroethyl-2,2,2-trifluoroethyl ether. By using the above substances as diluents, the diluents can effectively avoid having a significant impact on the solvation structure of the electrolyte, thereby reducing the viscosity of the electrolyte, improving the wettability of the electrolyte, and enhancing the ionic conductivity of the electrolyte; at the same time, the above substances all have non-polar structures and low donor capabilities. As diluents, they can effectively improve the antioxidant capacity of the electrolyte, and are also beneficial to enhancing the film formation stability of the SEI interface and the CEI interface, so as to improve the cycle stability and cycle life of lithium metal batteries.
[0069] In some embodiments, the ester compound A in the solvent includes at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, vinylene carbonate, methylene ethylene carbonate, methyl butyrate, ethyl propionate, trimethyl phosphate, triethyl phosphate, γ-butyrolactone, triallylamine, triallyl cyanurate, and triallyl isocyanurate; the ether compound A is a fatty ether and may include at least one of methyl n-butyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, ethylene glycol dibutyl ether, 1,2-dimethoxypropane, 1,3-dimethoxypropane, and allyl ether. The above-mentioned ester compound A or ether compound A as a solvent can make the electrolyte have a strong antioxidant ability, and the above-mentioned ether compound A as a solvent can make the electrolyte have good compatibility with metallic lithium, so as to facilitate the formation of a stable SEI interface layer.
[0070] In some embodiments, the concentration of the fluorine-containing lithium salt in the solvent is 4-8 mol / L, preferably 7 mol / L, to ensure that the electrolyte is a high concentration system.
[0071] It should be noted that as the lithium salt concentration in the traditional electrolyte increases, the wettability of the electrolyte becomes worse, the transmission of lithium ions in the electrolyte becomes more difficult, and the number of battery cycles is severely limited. The electrolyte provided in the embodiment of the present invention can ensure that the electrolyte is a high-concentration system, effectively inhibit the uneven stripping / deposition of metallic lithium, and improve the battery cycle stability and safety. At the same time, it improves the transmission efficiency of lithium ions in the electrolyte, thereby achieving an effective balance between battery cycle performance and safety performance.
[0072] In some embodiments, the fluorine-containing lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; optionally, the fluorine-containing lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorophosphate, lithium difluorobis(oxalate phosphate) and lithium tetrafluorooxalate phosphate. All of the above substances have good solubility, good hydrolysis resistance and temperature stability. After the above substances are dissolved in a solvent, they can form a fluorine-containing lithium salt / solvent complex with the solvent, so that the diluent can be miscible with the fluorine-containing lithium salt / solvent complex during the lithium metal battery cycle to improve the film formation stability of the SEI interface layer and the CEI interface layer.
[0073] Another embodiment of the present invention provides a method for preparing the above-mentioned electrolyte, wherein a fluorine-containing lithium salt, a solvent, and a diluent are mixed in a predetermined ratio to prepare the electrolyte.
[0074] Specifically, the electrolyte can be prepared by dehydrating the solvent and the diluent respectively, drying the fluorine-containing lithium salt at a drying temperature of 60° C., and mixing the dehydrated solvent, the diluent and the dried fluorine-containing lithium salt in a predetermined ratio.
[0075] In some embodiments, the method for preparing the electrolyte includes mixing a fluorine-containing lithium salt, a solvent, a diluent, and an additive based on a predetermined ratio to prepare the electrolyte.
[0076] Specifically, when the additive is an organic compound and / or an inorganic compound, the solvent, the diluent, the organic compound and / or the inorganic compound and the dried fluorine-containing lithium salt are mixed in a predetermined ratio to prepare an electrolyte.
[0077] Another embodiment of the present invention provides a battery, which is at least formed by the above-mentioned electrolyte assembly.
[0078] It can be understood that the battery in the embodiment of the present invention can be composed of lithium metal as the negative electrode and the electrolyte in the above embodiment; in other embodiments, the battery can also be composed of copper foil or graphite as the negative electrode and the electrolyte in the above embodiment; the batteries can have high cycle stability and safety.
[0079] The following examples describe the disclosure of the present application in more detail, and these examples are only used for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents and raw materials used in the examples are commercially available or synthesized according to conventional methods, and the instruments used in the examples are commercially available.
[0080] Example 1
[0081] ① Dehydrate ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0082] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) were fully mixed in a molar ratio of 1:1.2:3. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0083] Example 2
[0084] ① Dehydrate ethylene glycol dimethyl ether (DME) and decafluoropentane, put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0085] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and decafluoropentane were fully mixed in a molar ratio of 1:1.2:3. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0086] Example 3
[0087] ① Dehydrate ethylene glycol dimethyl ether (DME) and bis(2,2,2-trifluoroethyl) ether (BTFE), place in 4A grade molecular sieve, and let stand for 72 hours. Place bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) in a 60°C vacuum oven for 72 hours.
[0088] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and bis(2,2,2-trifluoroethyl) ether (BTFE) in a molar ratio of 1:1.2:3. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte is obtained. The concentration of fluorinated lithium salt in the electrolyte is 7M.
[0089] Example 4
[0090] ① Dehydrate ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0091] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) in a molar ratio of 1:1.2:1.2. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte is obtained. The concentration of fluorinated lithium salt in the electrolyte is 7M.
[0092] Example 5
[0093] ① Dehydrate ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0094] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) were fully mixed in a molar ratio of 1:1.2:3.6. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0095] Example 6
[0096] ① Dehydrate ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), put them into 4A molecular sieves, and let them stand for 72 hours. Put bistrifluorosulfonyl imide lithium salt (LiTFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0097] ② LiTFSI, DME and TTE were mixed in a molar ratio of 1:1.2:3. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of fluorinated lithium salt in the electrolyte was 7M.
[0098] Example 7
[0099] ① Dehydrate ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), put them into 4A molecular sieves, and let them stand for 72 hours. Put bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) into a 60°C vacuum oven and let them stand for 72 hours.
[0100] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), lithium salt of bis(trifluorosulfonyl)imide (LiTFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) were fully mixed in a molar ratio of 1:2:4.2:7.2. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0101] Example 8
[0102] ① Dehydrate ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), put them into 4A molecular sieves, and let them stand for 72 hours. Put bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) into a 60°C vacuum oven and let them stand for 72 hours.
[0103] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), lithium salt of bis(trifluorosulfonyl)imide (LiTFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) were fully mixed in a molar ratio of 2:1:4.2:7.2. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0104] Example 9
[0105] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydrofuran, put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0106] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydrofuran were fully mixed in a molar ratio of 1:1.2:3:0.2. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0107] Example 10
[0108] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydrofuran, put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0109] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydrofuran in a molar ratio of 1:1.2:3:2.8. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte is obtained. The concentration of fluorinated lithium salt in the electrolyte is 7M.
[0110] Embodiment 11
[0111] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydrofuran, put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0112] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydrofuran were fully mixed in a molar ratio of 1:1.2:3:0.4. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0113] Example 12
[0114] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and dioxolane (DOL), put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0115] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and dioxolane (DOL) were fully mixed in a molar ratio of 1:1.2:3:0.1. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0116] Example 13
[0117] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and isosorbide dinitrate (ISDN), put them into 4A molecular sieves and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0118] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and isosorbide dinitrate (ISDN) were fully mixed in a molar ratio of 1:1.2:3:0.03. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0119] Embodiment 14
[0120] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydropyran (THP), put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0121] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and tetrahydropyran (THP) were fully mixed in a molar ratio of 1:1.2:3:0.08. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0122] Embodiment 15
[0123] ① Dehydrate ethylene glycol dimethyl ether (DME) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) and lithium nitrate into a vacuum oven at 60°C and let them stand for 72 hours.
[0124] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and lithium nitrate in a molar ratio of 1:1.2:3.5:0.1. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte is obtained. The concentration of fluorinated lithium salt in the electrolyte is 7M.
[0125] Example 16
[0126] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and trioxymethylene, put them into 4A molecular sieves and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0127] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and trioxymethylene were fully mixed in a molar ratio of 1:1.2:3:0.1. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0128] Embodiment 17
[0129] ① Dehydrate ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) and trioxymethylene, put into 4A molecular sieve, and let stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) and lithium nitrate into a vacuum oven at 60°C and let stand for 72 hours.
[0130] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), trioxymethylene and lithium nitrate in a molar ratio of 1:1.2:2.4:0.1:0.1. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte is obtained. The concentration of fluorinated lithium salt in the electrolyte is 7M.
[0131] Comparative Example 1
[0132] ① Dehydrate ethylene glycol dimethyl ether (DME) and fluorobenzene, put into 4A grade molecular sieve, and let it stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0133] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and fluorobenzene in a molar ratio of 1:1.2:3, and stir for 12 hours to obtain a highly dispersed, clear and transparent high-concentration electrolyte. The concentration of fluorinated lithium salt in the electrolyte is 7M.
[0134] Comparative Example 2
[0135] ① Dehydrate dimethyl ether (DME) and m-fluorotoluene, put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0136] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and m-fluorotoluene in a molar ratio of 1:1.2:3, and stir for 12 hours to obtain a highly dispersed, clear, and transparent high-concentration electrolyte. The concentration of the fluorinated lithium salt in the electrolyte is 7M.
[0137] Comparative Example 3
[0138] ① Dehydrate dimethyl ether (DME) and trifluoromethoxybenzene, put them into 4A molecular sieves, and let them stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0139] ②Fully mix lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and trifluoromethoxybenzene in a molar ratio of 1:1.2:3, and stir for 12 hours to obtain a highly dispersed, clear, and transparent high-concentration electrolyte. The concentration of the fluorinated lithium salt in the electrolyte is 7M.
[0140] Comparative Example 4
[0141] ① Dehydrate ethylene glycol dimethyl ether (DME), put it into 4A grade molecular sieve, and let it stand for 72 hours. Put bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) into a 60°C vacuum oven and let it stand for 72 hours.
[0142] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and ethylene glycol dimethyl ether (DME) were fully mixed in a molar ratio of 1:2.4. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 4M.
[0143] Comparative Example 5
[0144] ① Dehydrate ethylene glycol dimethyl ether (DME), put it into 4A grade molecular sieve, and let it stand for 72 hours. Put bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) into a 60°C vacuum oven and let it stand for 72 hours.
[0145] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and ethylene glycol dimethyl ether (DME) were fully mixed in a molar ratio of 1:1.9. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 5M.
[0146] Comparative Example 6
[0147] ① Dehydrate ethylene glycol dimethyl ether (DME), put it into 4A grade molecular sieve, and let it stand for 72 hours. Put bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) into a 60°C vacuum oven and let it stand for 72 hours.
[0148] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and ethylene glycol dimethyl ether (DME) were fully mixed in a molar ratio of 1:1.6. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 6M.
[0149] Comparative Example 7
[0150] ① Dehydrate ethylene glycol dimethyl ether (DME), put it into 4A grade molecular sieve, and let it stand for 72 hours. Put bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) into a 60°C vacuum oven and let it stand for 72 hours.
[0151] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and ethylene glycol dimethyl ether (DME) were fully mixed in a molar ratio of 1:1.2. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0152] Comparative Example 8
[0153] ① Dehydrate ethylene glycol dimethyl ether (DME), put it into 4A grade molecular sieve, and let it stand for 72 hours. Put bis(fluorosulfonyl)imide lithium salt (LiFSI) and bis(trifluorosulfonyl)imide lithium salt (LiTFSI) into a 60°C vacuum oven and let it stand for 72 hours.
[0154] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and ethylene glycol dimethyl ether (DME) were fully mixed in a molar ratio of 1:1.1. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 8M.
[0155] Comparative Example 9
[0156] ① Dehydrate dimethyl carbonate (DMC), put it into 4A molecular sieve, and let it stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0157] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and dimethyl carbonate (DMC) were fully mixed in a molar ratio of 1:1.7. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0158] Comparative Example 10
[0159] ① Dehydrate ethyl methyl carbonate (EMC), put it into 4A molecular sieve, and let it stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0160] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and ethyl methyl carbonate (EMC) were fully mixed in a molar ratio of 1:1.2. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0161] Comparative Example 11
[0162] ① Dehydrate acetonitrile (AN), put it into 4A molecular sieve, and let it stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0163] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and acetonitrile (AN) were fully mixed in a molar ratio of 1:1.8, and stirred for 12 hours to obtain a highly dispersed, clear and transparent high-concentration electrolyte. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0164] Comparative Example 12
[0165] ① Dehydrate dimethyl sulfoxide (DMSO), put it into 4A molecular sieve, and let it stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0166] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and dimethyl sulfoxide (DMSO) were fully mixed in a molar ratio of 1:1.1. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0167] Comparative Example 13
[0168] ① Dehydrate dimethoxysilane (DMMS), put it into 4A molecular sieve, and let it stand for 72 hours. Put lithium bis(fluorosulfonyl)imide (LiFSI) into a vacuum oven at 60°C and let it stand for 72 hours.
[0169] ② The lithium salt of bis(fluorosulfonyl)imide (LiFSI) and dimethoxysilane (DMMS) were fully mixed in a molar ratio of 1:1.1. After stirring for 12 hours, a highly dispersed, clear and transparent high-concentration electrolyte was obtained. The concentration of the fluorinated lithium salt in the electrolyte was 7M.
[0170] The electrolytes prepared in the above-mentioned Examples 1 to 17 and Comparative Examples 1 to 3 were respectively used to carry out ion conductivity tests, and the test results are shown in Tables 1 to 3 below.
[0171] In addition, in order to verify the promoting effect of the electrolyte on the performance of the lithium metal battery in each embodiment, lithium nickel cobalt manganese oxide (NCM) was used as the positive electrode material, aluminum foil was used as the current collector, lithium nickel cobalt manganese oxide (NCM), adhesive polyvinylidene fluoride (PVDF), conductive agent (conductive carbon, single-walled carbon nanotubes, multi-walled carbon nanotubes) and organic solvent N-methyl-2-pyrrolidone were used as raw materials to prepare the battery positive electrode, and metallic lithium was used as the negative electrode. Under dew point conditions of -40°C, the high-concentration electrolytes prepared in the above embodiments 1 to 17 and comparative examples 1 to 3 were respectively used. The prepared electrolyte, battery positive electrode, ceramic diaphragm and negative electrode were assembled into a 2.3Ah lithium metal soft-pack battery, and the high-concentration electrolytes prepared in comparative examples 4 to 13 were respectively used to assemble Li||Cu half-cells in an argon atmosphere (O2 <0.1ppm and H2O <0.1ppm). The electrical performance of the batteries prepared in each embodiment and comparative example was tested, wherein the current density of the lithium-copper battery during the test was 1.13 mA / cm 2 The test results are shown in Table 4 and Attached Figures 1 to 10 shown.
[0172] Table 1. Statistical table of ion conductivity of electrolytes obtained in Examples 1 to 5 and Comparative Examples 1 to 3
[0173]
[0174] Table 2. Statistical table of ion conductivity of electrolytes obtained in Examples 6 to 8
[0175]
[0176]
[0177] Table 3. Statistical table of ion conductivity of electrolyte containing additives
[0178]
[0179] Table 4. Lithium-copper half-cell test data statistics
[0180]
[0181] The following combines Tables 1 to 4 and Figures 1 to 10 The performance of the batteries prepared by the electrolytes in the embodiments and comparative examples is analyzed. Figures 8 to 10 In the LSV (Linear Sweep Voltammetry) graph, the battery voltage changes linearly over time, and the corresponding current signal is measured at the same time. By analyzing the slope, peak potential, peak current and other parameters of the curve, the electrochemical performance of the battery can be evaluated; in this application Figure 6 The CV (Cyclic Voltammetry) curve can be used to evaluate the redox reaction and ion transfer process on the electrode surface to verify the stability of the battery.
[0182] Refer to Table 1 and Figures 1 to 5 As can be clearly seen from Table 1, the ionic conductivity and ion migration number of each electrolyte in Examples 1 to 5 are significantly higher than those of the electrolytes prepared in Comparative Examples 1 to 3, which verifies that the diluent in this embodiment can significantly promote the improvement of the ion conductivity of the electrolyte when the molar ratio of the fluorine-containing lithium salt, the solvent and the diluent is in the range of (0.8 to 1.8): (1 to 3): (1 to 5), while Comparative Examples 1 to 3 all use aromatic fluoroether as the diluent, and the ionic conductivity and ion migration number of the electrolyte are much lower than those of the electrolytes prepared in Examples 1 to 5 using TTE, HFC or BTFE as the diluent; further combined with Figure 1 to Figure 5 It can be found that the lithium metal soft-pack batteries prepared by the electrolytes of Examples 1, 3 and 5 are effectively improved in terms of the number of cycles and the capacity retention rate compared with the lithium metal soft-pack batteries prepared by the electrolytes of Comparative Examples 1 and 2, indicating that the diluent in this embodiment can effectively improve the cycle stability and cycle life of the lithium metal battery when the molar ratio of the fluorine-containing lithium salt, the solvent and the diluent is in the range of (0.8-1.8): (1-3): (1-5).
[0183] It should be noted that Example 1 is a preferred embodiment, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) is used as a diluent to prepare an electrolyte. The lithium metal soft-pack battery prepared by the embodiment shows a long cycle performance of more than 280 cycles, and the capacity retention rate is 90%, which is much higher than the lithium metal soft-pack battery prepared by each electrolyte in Comparative Examples 1 to 3. It shows that the introduction of TTE as a diluent into the electrolyte system can not only reduce the viscosity of the electrolyte and improve the conductivity, but also promote the film formation stability of SEI and CEI, so as to achieve the improvement of the cycle stability and cycle life of the lithium metal battery. In addition, TTE, as a preferred diluent for high energy density lithium metal battery systems, is lower in cost than BEFE and HFC, which is conducive to saving production costs and promoting the widespread application of lithium metal batteries.
[0184] Further referring to Table 1 and Table 2, TTE is used as a diluent in both Examples 1 and 6, wherein the fluorine-containing lithium salt of the electrolyte in Example 1 is only bis(fluorosulfonyl)imide lithium salt (LiFSI), and the fluorine-containing lithium salt of the electrolyte in Example 6 is only bis(trifluorosulfonyl)imide lithium salt (LiTFSI). Under the same concentration conditions, the ion conductivity of the electrolyte prepared in Example 6 is lower than that of the electrolyte prepared in Example 1. This is because the FS bond of LiFSI is easier to break than the CS bond in LiTFSI, so that LiFSI is easier to decompose, which makes the viscosity and wettability of the electrolyte in Example 1 higher, thereby improving the ion conductivity of the electrolyte; in addition, compared with Example 6, the cycle performance of the lithium metal soft-pack battery in Example 1 is better. This is because after the FS bond of LiFSI is broken, the fluorine atom has a certain protective effect on the aluminum foil, which makes the lithium metal battery more stable during the cycle.
[0185] Examples 7 and 8 are dual salt system electrolytes, i.e., fluorine-containing lithium salts use both LiFSI and LiTFSI, and both use TTE as a diluent. Example 8 has more LiTFSI than Example 7. The TFSI decomposed from LiTFSI has a large steric hindrance, which inhibits the decomposition of FSI, resulting in reduced stability of SEI, and thus poor cycle performance of the lithium metal battery.
[0186] For further reference, see Table 1, Table 3, Figure 1 , Figure 6 and Figure 7 , the electrolytes prepared in Examples 9 to 17 all have high ionic conductivity and ion migration number; among them, it can be found from Table 1 that the ionic conductivity and ion migration number of the electrolyte prepared in Example 9 are further improved compared with those in Example 1, and by Figure 6 and Figure 1It can be found that the lithium metal soft-pack battery prepared by the electrolyte of Example 9 has a significantly improved cycle number compared with Example 1, and the cycle number can be more than 340 cycles, and the cycle capacity retention rate after 340 cycles is still as high as 86%; Figure 6 Through the CV curve, it can be found that in Example 9, under the condition that the molar ratio of the fluorine-containing lithium salt, the solvent, the diluent and the additive is (0.8-1.8): (1-3): (1-5): (0.01-2), the electrolyte prepared with tetrahydrofuran as the additive undergoes anion preferential reduction reaction at 1.25V. This shows that the introduction of the additive in the above molar ratio range is beneficial to promote the preferential film formation of anions and inhibit the continuous reaction of highly active lithium metal with the electrolyte during the cycle. After modification with the additive, the electrolyte exhibits excellent film-forming properties during the cycle, thereby improving the ion conductivity of the electrolyte. At the same time, the cycle stability and cycle life of the lithium metal battery are significantly improved.
[0187] The only difference between Example 10 and Example 9 is the different amount of additives in the raw materials. The molar ratio of the fluorine-containing lithium salt, solvent, diluent and additive in Example 10 is not in the range of (0.8-1.8): (1-3): (1-5): (0.01-2). In particular, the molar content of the additive is too high. The ionic conductivity, ion migration number and cycle number of the obtained electrolyte are all lower than those in Example 9, indicating that the molar ratio of the fluorine-containing lithium salt, solvent, diluent and additive is in the range of (0.8-1.8): (1-3): (1-5): (0.01-2), which is more conducive to improving the ion conductivity of the electrolyte while significantly improving the cycle stability and cycle life of the lithium metal battery.
[0188] In order to evaluate the effect of the concentration of fluorine-containing lithium salt on the battery performance in the electrolyte using ether compound A as solvent, Comparative Examples 4 to 8 all use ether compound A ethylene glycol diethyl ether (DME) as solvent, and all use LiFSI as lithium salt. The concentration of lithium salt in the electrolyte of Comparative Examples 4 to 8 gradually increases; refer to Table 4 and Figure 8It can be found that when the molar ratio of the fluorinated lithium salt to the solvent is (0.8-1.8): (1-3), the concentration of the fluorinated lithium salt in the electrolyte is 4-8M, and each electrolyte is a high-concentration electrolyte. The average coulombic efficiency of the lithium-copper half-cell prepared by each electrolyte can reach more than 98.5% when it is cycled for 150 cycles. In particular, when the concentration of the fluorinated lithium salt in the electrolyte prepared in Comparative Example 7 is 7M, the average coulombic efficiency of the lithium-copper half-cell prepared by the electrolyte is as high as 99.5% when it is cycled for 150 cycles, indicating that a high-concentration electrolyte can be constructed within the range of (0.8-1.8): (1-3) to obtain a fluorinated lithium salt to the solvent, so that the electrochemical performance of the electrolyte in the lithium metal battery is more excellent, so as to ensure the uniform deposition and stable stripping of lithium after further compounding the diluent and additive, inhibit the growth of lithium dendrites, and promote the improvement of the cycle stability and cycle life of the lithium metal battery.
[0189] In order to evaluate the effect of ester compound A as a solvent on the performance of the electrolyte, the concentration of the fluorine-containing lithium salt in the electrolyte of Examples 9 to 13 is the same (all 7M), and the only difference is the specific choice of the solvent, that is, Example 9 uses ester compound A dimethyl carbonate (DMC) as a solvent, Example 10 uses ester compound A ethyl methyl carbonate (EMC) as a solvent, and Example 11 uses nitrile compound acetonitrile (AN) as a solvent, Example 12 uses sulfone compound dimethyl sulfoxide (DMSO) as a solvent, and Example 13 uses silane compound dimethoxysilane (DMMS) as a solvent.
[0190] Refer to Table 4 and Figures 9-10 By comparison, it can be found that the lithium-copper half-cells prepared by using the electrolytes of Comparative Examples 9 to 13 all have a high average coulombic efficiency, and the number of cycles of the lithium-copper half-cells prepared by the electrolytes of Comparative Examples 9 and 10 is significantly higher than that of Comparative Examples 11 to 13. Figure 9-10 It can be found that the oxidation resistance of the electrolytes of Comparative Examples 9 and 10 can reach above 5V. It can be understood that although ester compound A, nitrile compound, sulfone compound and silane compound all have good antioxidant ability, the electrolytes prepared by nitrile compound, sulfone compound and silane compound have poor compatibility with the metal lithium negative electrode, and are easily polymerized at the lithium metal negative electrode, and the generated polymer will inhibit the transmission of lithium ions. Therefore, using ester compound A as a solvent can effectively improve the ion conductivity of the electrolyte, while taking into account the cycle performance of the lithium metal battery.
[0191] In summary, the embodiments of the present invention design the raw materials for preparing the electrolyte, and the electrolyte is mainly made of fluorine-containing lithium salt, solvent and diluent; the molar ratio of fluorine-containing lithium salt, solvent and diluent is (0.8-1.8):(1-3):(1-5); or the electrolyte is made of fluorine-containing lithium salt, solvent, diluent and additive in a molar ratio of (0.8-1.8):(1-3):(1-5):(0.01-2), which effectively improves the cycle stability and safety of lithium metal batteries while taking into account the ion conductivity of the electrolyte, so as to promote the widespread application of lithium metal batteries.
[0192] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.
[0193] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte is mainly made of fluorine-containing lithium salt, solvent and diluent; Wherein, in the electrolyte, the molar ratio of the fluorine-containing lithium salt, the solvent and the diluent is (0.8-1.8):(1-3):(1-5).
2. The electrolyte according to claim 1, characterized in that The electrolyte also includes an additive; The additive includes at least one of an organic compound and an inorganic compound; Wherein, in the electrolyte, the molar ratio of the fluorine-containing lithium salt, the solvent, the diluent and the additive is (0.8-1.8): (1-3): (1-5): (0.01-2).
3. The electrolyte according to claim 1, characterized in that The solvent includes at least one of an ester compound A and an ether compound A; The diluent includes at least one of a halogenated alkane compound, an ester compound B and an ether compound B.
4. The electrolyte according to claim 2, characterized in that The organic compound has a monoether oxygen functional group and / or an unsaturated cyclic structure; Optionally, the inorganic compound includes at least one of a nitrogen-containing lithium salt and a lithium halide salt.
5. The electrolyte according to claim 4, characterized in that The additive satisfies at least one of the following a to c: a. The organic compound has any one or more of a three-membered ring, a four-membered ring, a five-membered ring or a six-membered ring, and the ring structure contains at least one ether bond; optionally, the ring structure has at least one substituent selected from alkyl, halogenated alkyl, nitro, hydroxyl and oxalylamino groups; b. The organic compound comprises at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran and trioxymethylene; c. The inorganic compound includes at least one of lithium nitrate, lithium fluoride, lithium bromide, lithium iodide and lithium chloride.
6. The electrolyte according to claim 5, characterized in that The additive is a mixture of at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, isosorbide dinitrate, tetrahydropyran, trioxymethylene and lithium nitrate.
7. The electrolyte according to claim 3, characterized in that The diluent satisfies at least one of the following conditions: d. The halogenated alkane compound includes at least one of decafluoropentane, methoxy nonafluorobutane, and ethoxy nonafluorobutane; e. The ester compound B includes a fluorinated carbonate, which may be selected from at least one of fluoroethylene carbonate, 1,2-bis(2-fluoroethoxy)ethane, methyl trifluoroethyl carbonate, ethyl difluoroacetate, ethyl trifluoroacetate, tris(2,2,2-trifluoroethyl)orthoformate, methyl pentafluoropropionate, and ethyl pentafluoropropionate; f. The ether compound B includes a fluoroether, which can be selected from at least one of 2,2-bis(trifluoromethyl)-1,3-dioxolane, tetrafluoro-1-(2,2,2-trifluoroethoxy)ethane, methoxyperfluorobutane, 1,1,1,3,3,3-hexafluoroisopropyl methyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, and 1,1,2,2,-tetrafluoroethyl-2,2,2-trifluoroethyl ether.
8. The electrolyte according to claim 3, characterized in that The solvent satisfies at least one of the following g to h: g. the ester compound A comprises at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, vinylene carbonate, methylene ethylene carbonate, methyl butyrate, ethyl propionate, trimethyl phosphate, triethyl phosphate, γ-butyrolactone, triallylamine, triallyl cyanurate, and triallyl isocyanurate; h. The ether compound A includes aliphatic ether, which can be selected from at least one of methyl n-butyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, ethylene glycol dibutyl ether, 1,2-dimethoxypropane, 1,3-dimethoxypropane, and allyl ether.
9. The electrolyte according to claim 1, characterized in that The concentration of the fluorine-containing lithium salt in the solvent is 4-8 mol / L.
10. The electrolyte according to claim 1, characterized in that The fluorine-containing lithium salt includes at least one of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; Optionally, the fluorine-containing lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate.
11. A method for preparing an electrolyte according to any one of claims 1 to 10, characterized in that: The electrolyte is prepared by mixing a fluorine-containing lithium salt, a solvent, and a diluent based on a predetermined ratio; Optionally, the electrolyte is prepared by mixing a fluorine-containing lithium salt, a solvent, a diluent and an additive based on a predetermined ratio.
12. A battery, characterized in that: The battery is at least made of the electrolyte assembly according to any one of claims 1 to 10.
Citation Information
Cited By
Electrolyte for sodium-ion battery without negative electrode and sodium-ion battery without negative electrode
CN122552627A